Expressed emotion in panic disorder: Relationship with demographic and clinical variables and quality of life. (June 2016) - Demir, Meral Oran; Yıldız, Mesut; Batmaz, Sedat; Semiz, Murat; Songur, Emrah; Çakmak, Selcen; Demir, Osman
Objective: Expressed emotion (EE) predicts the outcome of treatment in patients with anxiety disorders. We aimed to investigate the relationship between EE and demographic and clinical characteristics of patients with panic disorder (PD), to determine whether there is a difference between PD, major depressive disorder (MDD) patients and healthy controls (HC) in terms of EE and to investigate the effect of EE on quality of life (QOL) in patients with PD. Methods: Our study involved a total of 150 participants (50 patients in each group). All participants were given the Level of Expressed Emotion (LEE) scale and the short-form health survey (SF)-36 . Furthermore, the EE scale was completed by the participant's key relatives. Results: EE was associated with some sociodemographic and clinical variables in patients with PD. There was no significant difference between PD and MDD and between PD and HC in terms of the LEE and the EE and their subscale scores. It was also demonstrated that EE had no effect on the QOL in patients with PD. Conclusion: EE was not different in PD compared to MDD and HC. Additionally, EE was not related to QOL in PD.